Secondary syphilis with HIV infection in men who have sex with men (MSM) patient treated with azithromycin and doxycycline: a case report - Hani Lusyana; Agus Walujo; Lina Damayanti (Bali Dermatology and Venereology Journal, 2021)
Introduction: Syphilis frequently presents in tandem with conditions such as HIV, and the prevalence is increasing, particularly in men who have sex with men (MSM). The most common and recognizable manifestations are usually the secondary stage, characterized with or without constitutional symptoms. Choosing the first line or alternative therapy was based on patient condition and the availability of the medicine.Case report: It was reported a 22-year-old man with secondary syphilis and HIV infection. The diagnosis was established based on erythema and hyperpigmented maculopapular lesions with the scale on the forearms, palms, back, feet, and soles without pruritic sensation, a history of the same-sex sexual partners and the titer of VDRL 1:64, TPHA 1:2560. The patient also has a low CD4 level, and HIV-1 RNA was detected on a blood test. Patients received azithromycin 2 grams orally and continued by doxycycline twice a day for 30 days and also treated for the HIV Infection.Conclusion: Skin disorders have improved rapidly and significantly, accompanied by decreased VDRL titer.